(3deM GdedMs - (3SYO Hf Ydj Hf GdbGSe GdCfUGQj GdNRQLj GdMXjQj, CHh GdeYGdj (B( (3nOnqdGd GdocoJH (B)(3,J (B568 (3g` s
(3ChdgG (B:s
(3hHYO aCYPH GdcdGe hbO LeYJ cJGHkG s
(3BNQgG (B:s
(3ef LGfi eSJNHQkG Yf Ydeg hGddg Yde cd SQ s
(3GdfSNI HgG MhGTs
(3JcQQ CjVkG JMJ Qbe (B" 78" (3HdGZIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B86 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B212s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1560s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdHdGZIs